KONSEP ISLAM TENTANG SUPERVISI PENDIDIKAN - Meti Fatimah; Sudarto; Fajarullah Al Ghifari (INOVASI : Jurnal Ilmiah Pengembangan Pendidikan, 2025)
This article aims to illustrate the basic concept of supervision from an Islamic educational perspective. The method used is library analysis to explain supervision from an Islamic perspective. Islamic educational supervision aims to develop religious potential or innate nature by internalizing the values contained in the Quran and the hadith of the Prophet Muhammad. There is Allah's supervision of His servants, which encompasses all human deeds and actions directly. Allah also supervises through angels who record all human words and actions. Furthermore, there is self-supervision, where our limbs will speak for everything we do while living in this world. Fourth, supervision is through the Sunnah of the Prophet Muhammad, who has provided a living example and guided all aspects of life comprehensively.